2021
DOI: 10.1371/journal.pone.0258796
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of lumbar support with built-in massager system on spinal angle profiles among high-powered traffic police motorcycle riders: A randomised controlled trial

Abstract: Traffic police riders are exposed to prolonged static postures causing significant angular deviation of the musculoskeletal, including the lumbar angle (L1-L5). This postural alteration contributes to awkward posture, musculoskeletal disorders and spinal injury, especially in the lower back area, as it is one of the most severe modern diseases nowadays. Thus, the study aimed to evaluate the effect of lumbar support with a built-in massager system on spinal angle profiles among traffic police riders. A randomis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Our results also found several high-impact articles that employed the quasi-experimental method to compare the control group with the main group or other relevant groups (Dhole et al, 2021;Esmaeili et al, 2023;Heidarimoghadam et al, 2020;Hijam et al, 2020;Lin et al, 2022;Mohammad Yusof et al, 2021;Motamedzadeh et al, 2021;So et al, 2019;Yang et al, 2021). Such an approach allows for a rigorous examination of the effects of interventions and facilitates a comprehensive analysis of the research findings.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Our results also found several high-impact articles that employed the quasi-experimental method to compare the control group with the main group or other relevant groups (Dhole et al, 2021;Esmaeili et al, 2023;Heidarimoghadam et al, 2020;Hijam et al, 2020;Lin et al, 2022;Mohammad Yusof et al, 2021;Motamedzadeh et al, 2021;So et al, 2019;Yang et al, 2021). Such an approach allows for a rigorous examination of the effects of interventions and facilitates a comprehensive analysis of the research findings.…”
Section: Discussionmentioning
confidence: 54%
“…Findings from the synthesis analysis indicated that ergonomic interventions have been frequently employed in Asian countries via three distinct approaches: device or tool-based interventions, administrative interventions, and a combination of both. As shown in Table 4, seven articles explored the utilization of devices or tools as a means of ergonomic intervention (Alipour et al, 2021;Antwi-Afari et al, 2021;Arunkumar et al, 2019;Darliana et al, 2020;Kong et al, 2023;Mohammad Yusof et al, 2021;Ramdan & Candra, 2021), seven articles focused on the use of administration (Alghadir et al, 2021;Anshasi et al, 2022;Dhole et al, 2021;Heidarimoghadam et Hijam et al, 2020;Lin et al, 2022;Rahman et al, 2019), and eight articles used a combination of both approaches (Esmaeili et al, 2023;Kee, 2022;Motamedzadeh et al, 2021;Rostami et al, 2022;So et al, 2019;Susihono & Adiatmika, 2021;Susihono & Gede, 2020;Yang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation